Isolation of RNA from residual BD SurePath™ liquid-based cytology specimens and detection of HPV E6/E7 mRNA using the PreTect™ HPV-Proofer assay - Dixon, Eric P.; King, Lorraine M.; Adams, Melissa D.; Grønn, Petter; Murphy, Patricia G.; Brown, Charlotte A.; Brough, George H.; Skomedal, Hanne; Malinowski, Douglas P.; Fischer, Timothy J. (Journal of virological methods, 2008)
Infection with high-risk human papillomavirus (HPV) is known to be associated directly with the development of cervical cancer. Recent data suggests that the detection of E6/E7 mRNA from high-risk HPV types may serve as a better diagnostic method for detecting the presence of cervical pre-cancer than HPV DNA testing. This report details a commercially available nucleic acid isolation protocol which can be used to isolate reproducibly RNA from residual BD SurePath™ liquid-based cytology specimens stored for up to 28 days, and have demonstrated the quality and quantity of mRNA is sufficient for detection with the NorChip PreTect™ HPV-Proofer assay. Of the 242 specimens tested in this study, 236 (97.5%) tested positive for U1A internal control gene expression. HPV type 16, 18, 31, 33 or 45 mRNA was detected in 16/20 (80%) of the analyzed high-grade squamous intraepithelial lesion (HSIL) specimens, with a low frequency of HPV mRNA detected in the normal lesions (3%). The presence of HPV E6 expression in a subset of HPV positive specimens was also detected by real-time RT-PCR. These findings confirm that RNA of sufficient quality can be isolated from residual BD SurePath™ cervical cytology specimens for use in downstream NASBA and RT-PCR-based assays.